Scientific Publication Ethics - Osman İnci (Türk Kütüphaneciliği)
Science based on consciousness of responsibility and principles of trust puts academics under an obligation to act according to the values and principles, ethical attitudes and standards of behaviour. A quest for perfectness, to observe truth and show respect for the dignity and value of each individual should be a fundamental principle. In this context, academic freedom and autonomy, academic integrity,  responsibility and accountabily, respect for others, the protection of the fundamental rights and competence are among the core values of academic merit.